Generation of trapezoidal envelope pulses and soliton rains from passively mode-locked fiber laser with MoS2 saturable absorber on microfiber. (27th June 2018) - Wang, Zhenhong; He, Ruijing; Liu, Yan-ge; Zhang, Hao; Han, Simeng; Li, Hongye; Wang, Guangdou; Yang, Guang; Wang, Zhi
Abstract: We report the generation of trapezoidal envelope pulses and soliton rains in an erbium-doped fiber laser with an MoS2 -deposited microfiber saturable absorber. The pulse duration of the trapezoidal envelope pulses increases from 7 to 95 ns with the increment of the pump power. The maximum intracavity pulse energy is as high as 34 nJ. At a low pump power, the proposed laser can be switched to the soliton-rains regime by properly changing the polarization states. The microfiber-based MoS2 all-fiber laser can serve as an optical source with improved pulse energy for potential applications in nonlinear dynamics.